2018
DOI: 10.3122/jabfm.2018.03.170273
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Implementation of Complex Interventions in Primary Care Teams

Abstract: Background:The implementation of interventions to support practice change in primary care settings is complex. Pragmatic strategies, grounded in empiric data, are needed to navigate real-world challenges and unanticipated interactions with context that can impact implementation and outcomes.Objective: This article uses the example of the "5As Team" randomized control trial to explore implementation strategies to promote knowledge transfer, capacity building, and practice integration, and their interaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…1 Tackling one element in isolation, however, may produce undesirable consequences in another. 2,3 Meanwhile, physician and medical staff burnout represents an existential threat to the primary care workforce. One-half of all primary care physicians report symptoms of burnout, and 1 in 3 would not choose their specialty again.…”
Section: Introductionmentioning
confidence: 99%
“…1 Tackling one element in isolation, however, may produce undesirable consequences in another. 2,3 Meanwhile, physician and medical staff burnout represents an existential threat to the primary care workforce. One-half of all primary care physicians report symptoms of burnout, and 1 in 3 would not choose their specialty again.…”
Section: Introductionmentioning
confidence: 99%
“…Aligning with our expert participants, the literature supports that implementation is a dynamic process which does not unfold in a linear fashion [17]. As a result of the Delphi, our process model acknowledges that moving evidence into practice is complex and often unpredictable and is in uenced by many factors [18].…”
Section: Summary Of Key Ndingsmentioning
confidence: 54%
“…The authors advocated for more research to develop a theoretical base for intervention selection or development and for tailoring interventions, based on identi ed barriers and facilitators, to increase their effectiveness [20][21]. In addition, the importance of aligning theories or frameworks with the intervention is noted in the literature [17]. Research has identi ed that clinical outcomes are improved when theories or frameworks guide the implementation process, with speci c attention paid to the t with context [22].…”
Section: Summary Of Key Ndingsmentioning
confidence: 99%
“…Baskerville et al concluded in their systematic review that primary care practices are nearly 3 times more likely to adopt evidence-based guidelines through practice facilitation when there is tailoring of the intervention [7]. Qualitative studies of primary care practice facilitation of complex interventions echo the importance of facilitating team communication, iterative evaluation of the implementation process with real-time feedback, facilitator integration into the practices, and flexibility [43,44].…”
Section: Discussionmentioning
confidence: 99%